2000
DOI: 10.4141/s99-050
|View full text |Cite
|
Sign up to set email alerts
|

Active carbon pools and enzyme activities in soils amended with de-inking paper sludge

Abstract: . 2000. Active carbon pools and enzyme activities in soils amended with de-inking paper sludge. Can. J. Soil Sci. 80: 99-105. Application of paper mill wastes generally improves soil organic matter content, biological activity and physical properties. However, the impact of large application rates (>50 Mg ha -1 ) on soil microflora and their activity has not been assessed. A field study was undertaken on a well-drained clay loam and a poorly drained silty clay loam amended with de-inking paper sludge (DPS) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 31 publications
1
17
0
2
Order By: Relevance
“…These results support the earlier studies, which also found positive effects of raw and composted de-inking sludges on soil microbial biomass and enzyme activities (Simard et al 1998bChantigny et al 2000;Gagnon et al 2000). In our study, neither acid nor alkaline phosphatase activity was significantly (r = 0.15 -0.19, P > 0.05) correlated to Mehlich-3 extractable soil P content.…”
Section: Soil Enzyme Activitiessupporting
confidence: 82%
“…These results support the earlier studies, which also found positive effects of raw and composted de-inking sludges on soil microbial biomass and enzyme activities (Simard et al 1998bChantigny et al 2000;Gagnon et al 2000). In our study, neither acid nor alkaline phosphatase activity was significantly (r = 0.15 -0.19, P > 0.05) correlated to Mehlich-3 extractable soil P content.…”
Section: Soil Enzyme Activitiessupporting
confidence: 82%
“…For example, incorporation of a combined sludge at 246 Mg ha -1 , having a water holding capacity of 0.19 and 0.12 cm 3 cm -3 at -33 and -1500 kPa, increased soil water 20 and 74% at -33 and -1500 kPa, respectively (Zhang et al 1993). Soil water contents of a silty clay loam and a clay loam were increased by 50 and 100 Mg ha -1 deinking sludge from 271 to 726 d after sludge application, compared with the unamended control (Chantigny et al 2000a). Increased total soil water may create more favorable conditions for soil organisms, particularly during drought (Chantigny et al 2000a).…”
Section: Soil Water Holding Capacitymentioning
confidence: 85%
“…Soil water contents of a silty clay loam and a clay loam were increased by 50 and 100 Mg ha -1 deinking sludge from 271 to 726 d after sludge application, compared with the unamended control (Chantigny et al 2000a). Increased total soil water may create more favorable conditions for soil organisms, particularly during drought (Chantigny et al 2000a).…”
Section: Soil Water Holding Capacitymentioning
confidence: 92%
See 1 more Smart Citation
“…Organic matter is involved in the enhancement of soil quality since it acts on soil structure, nutrient storage and biological activity [2] . The application of organic fractions of urban wastes (e.g., sewage sludge and municipal solid wastes) as organic amendments to agricultural soils of these areas may be of use in improving their quality and be considered an attempt to alleviate the serious environmental and health problems caused by their accumulation [3] . Aggregation and Soil Organic Carbon (SOC) concentrations represent integrative effects of soil type, environment and soil management practices including crop rotation, tillage and fertilizer management [4] .…”
Section: Introductionmentioning
confidence: 99%